Analisis Kesulitan Belajar Peserta Didik Kelas 5 pada Mata Pelajaran PAI di SDN Candi Burung 2 Pamekasan - Nailatur Rizqiyah; Masti Yanto; Waqiatul Masruroh; Moh Elman (INDO PUBLISHING, 2025)
The aim of this research is to determine the learning difficulties of grade 5 students in PAI subjects at SDN Candi Burung 2 Pamekasan. This paper uses a qualitative method with a descriptive type. The subjects of this research were 5th grade students at SDN Candi Burung 2 Pamekasan. Meanwhile, the results of this research can be concluded that the forms of learning difficulties faced by grade 5 students in PAI subjects at SDN Candi Burung 2 Pamekasan include: difficulty focusing when learning takes place and difficulty absorbing learning material. Learning difficulties are caused by two factors, namely internal and external. Internal factors include: low interest in learning and intelligence of participants. Meanwhile, external factors include lack of parental guidance. The efforts made by PAI teachers to overcome these learning difficulties are by implementing learning innovations and communicating students' learning progress to their parents.